The Promise of Artificial Intelligence and Potential Impact on the Sales Function: A Sustainability Perspective - Plank, Richard E. (Journal of Strategic Innovation and Sustainability, 2020)
After a great deal of press and promise, artificial intelligence is beginning to make inroads in the sales function. In this paper, we follow one United Kingdom-based company called Cloudapps and the firm’s development of an artificial intelligence solution to address the issues inherent in the management of the sales pipeline. We then outline how the use of this technology can help the firm both manage their pipeline as well as develop sustainable value propositions for their current and potential clients. In doing so we also point out the importance of gaining experience and using incremental compensation, in helping to gain the benefits that AI potentially provides.